Handbook of Plant Biotechnology 2004
DOI: 10.1002/0470869143.kc020
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Resistance to Insect Pests

Abstract: With a projected increase in world population to 10 billion over the next four decades, an immediate priority for agriculture is to achieve maximum production of food and other products in a manner which is environmentally sustainable and cost effective. Despite the synthesis of improved pesticides, and integrated pest management strategies, yield losses due to insects have actually increased slightly for most crops over the last two decades. The concept of utilising a transgenic approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 157 publications
0
12
0
Order By: Relevance
“…To increase pest control efficacy and delay resistance evolution, a gene pyramiding strategy has been employed in transgenic plants to produce two or more Bt toxins of dissimilar mode of action effective against the same target pest species [81][82][83]. Thus, crops pyramided with Bt genes express the insecticidal toxin in all of their tissues.…”
Section: Genetic Engineering Methods For Gene Pyramidingmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase pest control efficacy and delay resistance evolution, a gene pyramiding strategy has been employed in transgenic plants to produce two or more Bt toxins of dissimilar mode of action effective against the same target pest species [81][82][83]. Thus, crops pyramided with Bt genes express the insecticidal toxin in all of their tissues.…”
Section: Genetic Engineering Methods For Gene Pyramidingmentioning
confidence: 99%
“…Thirdly, the pathogen avirulence (Avr) gene undergoes strong diversifying selection pressure or mutation to avoid recognition by host (R) genes [81]. The low levels of pathogenic resistance by some transgenic crops coupled with the negative perception of genetically modified plants have resulted in a relatively small number of transgenic lines being brought to late stage field testing and even fewer that have been successfully brought to market.…”
Section: Genetic Engineering For Pathogen Resistancementioning
confidence: 99%
“…Studies on adults and larvae of the two ladybird beetles Adalia bipunctata (Walker et al, 1998) and H. axyridis (Ferry et al, 2003;both Coleoptera: Coccinellidae) and the stinkbug Perillus bioculatus (Hemiptera: Pentatomidae) revealed that their major digestive proteolytic activity is cysteine-based (Ashouri et al, 1998;Overney et al, 1998). In contrast, carabid beetles have been found to rely upon serine proteases (both trypsin-like and chymotrypsin-like) for protein digestion (Gooding and Huang, 1969;Terra and Cristofoletti, 1996;Ferry et al, 2005) and N. brevicollis adults exhibited both serine and cysteine digestive protease activity .…”
Section: Protease Inhibitorsmentioning
confidence: 99%
“…Examples include: the ladybird H. axyridis (Ferry et al, 2003), different carabid beetles Ferry et al, 2005;Mulligan, 2006) and the predatory stinkbug P. bioculatus (Bouchard et al, 2003a,b). Indirect evidence for such an adaptation is also reported for larvae of C. carnea.…”
Section: Protease Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation